WHAT SERVICESCAPES SHOULD BE PRIORITIZED IN THE HOSPITALITY CENTER, UNIVERSITAS NEGERI PADANG? - Pasaribu, Pasaribu; Putra, Trisna; Lisna, Yuke Permata (Institut Pariwisata dan Bisnis Internasional, 2018)
The Hospitality Center is one of the business incubators managed by the Faculty of Tourism and Hospitality of the UNP. Currently, the Hospitality Center provides lodging services and will be equipped with other supporting facilities. Consumers who become the market share of this accommodation are University guests, trainees, students and employees, especially those in Padang State University. As one of the business incubators since UNP changed its status to a Public Service Agency, this unit is expected to be one of the pioneers of income generating which can contribute significantly to the income of the UNP. To increase Occupancy and maximize revenue and Hospitality Center, it is necessary to study the servicescape that is needed (Importance) by guests and how the performance (performance) of the servicescape itself has been provided by the manager. This study seeks to assess the level of importance and performance of each item from servicescapes consisting of ambient conditions, spatial layout and functionality, sign, symbol, and artifacts. The purpose of this study is; to determine the level of importance and performance of servicescapes, so that it can facilitate the assessment and help take action on servicescapes that have been analyzed and grouped into importance performance analysis, it can assess the condition of existing servicescapes and can make priority scales future improvements. The research method used in this study was descriptive method with a quantitative approach by distributing questionnaires to 80 guests who had or were staying at the Hospitality Center, Padang State University. The results of the research trials show that there were no declarations from the instruments prepared. The results of the study show that all the attributes of servicescapes belong to the B quadrant (Maintain Achievement), where the level of importance of servicescapes required by guests, has been met by the manager.